2001
DOI: 10.1097/00007890-200105270-00011
|View full text |Cite
|
Sign up to set email alerts
|

??-Cell Dysfunction Rather Than Insulin Resistance Is the Main Contributing Factor for the Development of Postrenal Transplantation Diabetes Mellitus

Abstract: These results revealed that fasting and 2-hr plasma glucose levels, as well as the proinsulin/insulin ratio before transplantation, are both possible indicators of beta-cell dysfunction and may be predictors for the development of PTDM. Furthermore, beta-cell dysfunction, rather than insulin resistance, was proven to be the main factor for the pathogenesis of PTDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 35 publications
8
97
2
6
Order By: Relevance
“…The VDR polymorphism is also reported to affect insulin secretion (30 -32). Their results and the results of this study are consistent with our previous reports (10,15), in that a defect in insulin secretion plays a more crucial role than increased insulin resistance in the pathogenesis of PTDM.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The VDR polymorphism is also reported to affect insulin secretion (30 -32). Their results and the results of this study are consistent with our previous reports (10,15), in that a defect in insulin secretion plays a more crucial role than increased insulin resistance in the pathogenesis of PTDM.…”
Section: Discussionsupporting
confidence: 94%
“…Although many studies have reported that insulin resistance is important to the pathophysiology of PTDM, a defect in insulin secretion may also play a role in the development of PTDM (10,15). Insulin is stored in pancreatic ␤-cells as zinc-insulin crystals.…”
mentioning
confidence: 99%
“…In the current study, the 39% incidence of PTDM at 1 year was very high and was even higher than the 23.7% we reported in our previous CsA-based study (6). In the previous study, we used the World Health Organization (WHO) criteria to define NGT (both FPG and 2-h postload glucose Ͻ7.8 mmol/l) and PTDM (FPG Ն7.8 mmol/l or 2-h postload glucose Ն11.0 mmol/l), whereas, in the current study, we defined NGT and PTDM according to American Diabetes Association criteria (8).…”
Section: Incidences Of Different Categories Of Ptdmcontrasting
confidence: 77%
“…The development and progression of PTD and its associated complications may be delayed by readily available interventions that are proved to be beneficial, such that early detection is likely to be important. IGT is also common posttransplantation with reported prevalence rates as high as 35% at 10 wk posttransplantation, 31 to 45% at 1 yr posttransplantation, and 13% at 6 yr posttransplantation (1,21,22). In the general population, asymptomatic IGT is an independent risk factor for all-cause mortality and of cardiovascular mortality in some studies (9 -11,23-25).…”
Section: Ptd and Igt In Rtrmentioning
confidence: 99%